UNBOXING “ICBP” BUSINESS DURING PANDEMIC: HAS PRICE REFLECTED ACCOUNTING INFORMATION? - Tangguh Bakit Prastyawan; Asqolani; Resi Ariyasa Qadri (Universitas Airlangga, 2022)
This study aims to determine the intrinsic value of PT Indofood CBP Sukses Makmur, Tbk equity during the Covid-19 pandemic. The research employed the qualitative approach utilizing the explanatory case study framework to achieve the research objective. The purposive sampling method was used to determine a single sample public firm as the study object which was chosen from the population of 677 public firms listed in Indonesia Capital Market per beginning 2020. The data collection was focused on gathering financial data related to the firm’s business activities. The data gathered was examined using the fundamental analysis framework which includes seven analyses on the business environment and the competition in the food-beverage industry in Indonesia; the firm competitive positioning; the company's growth strategy; the environmental, social, and government policy; the risks of the share ownership; the financial ratios; and the appraisal of entity’s intrinsic value. The results of our study indicated that the fair value of ICBP equity during the pandemic was undervalued. This research contributes to supporting the efficient market theory by proving that the firm market price has not reflected all accounting information, meaning that Indonesia's capital market remained in a semi-strong efficient state during the outbreak. The study implies, in a practical manner, that investors may adopt research findings to improve their decision on long-term equity investment in ICBP shares.